The soviet power’s attitude to the Latvian Orthodox Church in 1940–1941 - Gavrilin Aleksandr (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The analysis of the Soviet regime’s church policy in the territory of Latvia in 1940– 1941 till now has been limited to the “a priori” thesis about the pejorative attitude of a communistic ideology to a religion and a Church. The author investigates the basic directions of this policy in relation to the Latvian Orthodox Church (further — LOC). According to the author, in 1940–1941 on Latvia’s territories the Soviet power’s politics in relation to LOC can be divided into three basic periods: 1) June, 1940 — January, 1941 — the period of administrative, psychological and economic pressure upon believers and clergy; 2) February — May, 1941 — the period of a rigid psychological pressure and the taxation’s increasing of a church property; 3) June, 1941 — the beginning of undisguised repressions against a clergy the jurisdiction of Latvian Church was changed from the autonomy under the Constantinople Patriarchy to the Latvian diocese of the Moscow Patriarchy. The management of the Church was changed too: the Head of Latvia’s and Estonia’s exarchate Sergiy (Voskresensky), the metropolitan of Vilensk and Lithuanian, instead of Augustine (Peterson), the metropolitan Riga and Latvia. Generically, the orthodox believers and clergy endured this most complicated time with advantage. Moreover, the persecutions that were developed against the Church assisted the believers in rallying round the clergy and the clergy — round the church management such as a Diocesan council and a Exarch’s administration. Keywords: the Latvian Orthodox Church, Church-state relation, metropolitan Sergiy (Voskresensky), metropolitan Augustine (Petersons), the Soviet regime in Latvia in 1940–1941.